Prevention of Healthcare Associated Infections as an Effort to Increase Knowledge on How to Wash Hands for Patients of Grandmed Lubuk Pakam Hospital - Sirait, Reni Aprinawaty (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2024)
Wash your hands regularly with soap and water or use an alcohol-based hand sanitizer. Hand hygiene must be carried out before and after contact with patients, before carrying out aseptic procedures, after exposure to body fluids, and after touching objects around the patient, which is a crucial step in maintaining the safety of patients, health workers, visitors and the community around health care facilities. This activity took place at Grandmed Lubuk Pakam Hospital. This activity was aimed at 96 patients in the hospital, with the aim of increasing knowledge regarding preventing HAIs by washing hands properly. One very effective method for preventing the spread of infection is washing hands with soap and using hand sanitizer. Lack of knowledge about efforts to prevent exposure to infectious diseases can influence the frequency of disease occurrence. This activity is carried out through counseling which involves the use of learning videos and direct practice using hand sanitizer. In service activities by providing education related to material on the meaning of hand washing, the importance of washing hands in hospitals, the right time and mandatory hand washing for hospital patients, correct hand washing techniques, use of hand sanitizer, visuals and demonstrations, and education for families and visitors. In this activity, patients are asked to practice correct hand washing procedures. The results of the activity were obtained from 96 people, 85 people (89%) understood how to wash their hands properly as an effort to prevent and prevent the risk of infection while in hospital or after leaving the hospital. It is hoped that hospital management will work together with the Infectious Disease Prevention Committee (PPI) officers periodically to prevent and overcome the occurrence of nosocomial infections (HAIs) in the hospital.